1985
DOI: 10.1017/s002202990002447x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content of milk and milk products: water soluble vitamins in baby milk formulae

Abstract: SUMMARYA study of the content of water soluble vitamins in the 12 baby milk formulae available in the UK in April 1983 showed that levels of vitamins in the individual brands were generally in excess of those declared by the manufacturer. For cows' milk based formulae the mean excess of vitamins over the declared level was 94%. Vitamin levels in prepared formulae averaged three times the minimum recommended level. The average level of B vitamins in prepared cows' milk based formulae was six times higher than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…. Bishop (1985) found a mean excess of 188.7% over the manufacturer's stated level in 12 infant formula available in the UK (range from 60.0 to 469.4%) and Martin and others (1987) found in 76 infant formula from the United States, amounts that were in excess of label claims by 172.3% for thiamin and 176.2% for riboflavin. However, Martin and others also found some formula containing lower levels of these vitamins than the stated amounts.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…. Bishop (1985) found a mean excess of 188.7% over the manufacturer's stated level in 12 infant formula available in the UK (range from 60.0 to 469.4%) and Martin and others (1987) found in 76 infant formula from the United States, amounts that were in excess of label claims by 172.3% for thiamin and 176.2% for riboflavin. However, Martin and others also found some formula containing lower levels of these vitamins than the stated amounts.…”
Section: Resultsmentioning
confidence: 91%
“…Studies have reported water-soluble and fat-soluble vitamin contents and their stability during storage in liquid and in powdered cow's milk (Le Maguer and Jackson 1983;others 1984a, 1984b;Boer and others 1984;Woollard and Fairweather 1985;Scott and Bishop 1986;Renner 1988;Fellman and others 1991;Vidal-Valverde and others 1992), but few data on the usual contents of water-soluble and lipid-soluble vitamins in infant milks have been reported (Scott and Bishop 1985;Landen and others 1985;Martin and others 1987;Razagui and others 1992;Albalá-Hurtado and others 1999). No data were found in the literature on the stability of vitamins in infant milks during storage, except those reported by us (Albalá-Hurtado and others 2000) in three liquid Spanish infant milks.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies concerned with the vitamin content of human milk have been reported from various parts of the world (Hartman and Dryden 1965, Goldsmith et al 1983, Kim et al 1990, Scott and Bishop 1985, Herting and Drury 1969.…”
Section: Introductionmentioning
confidence: 99%
“…These have included studies on bulk liquid milk (Scott et a1 1984;Florence et a1 1985); baby milk formula (Scott and Bishop 1985); retail milk and milk products (Scott and Bishop 1986); and the concluding studies reported in this and the preceding paper (Scott and Bishop 1988) on cheeses, creams, ice creams and milk shakes.…”
Section: Generalmentioning
confidence: 99%
“…During the period 1980 to 1985 the Ministry of Agriculture, Fisheries and Food in London commissioned a number of long-term studies to provide detailed nutritional analysis and compositional information on a wide range of milk products. These have included studies on bulk liquid milk (Scott et a1 1984;Florence et a1 1985); baby milk formula (Scott and Bishop 1985); retail milk and milk products (Scott and Bishop 1986); and the concluding studies reported in this and the preceding paper (Scott and Bishop 1988) on cheeses, creams, ice creams and milk shakes.…”
Section: Generalmentioning
confidence: 99%